The mean increases by two.
15+23+24+26+27+35 = 140
140/6 = 23.3
23+24+26+27 = 100
100/4 = 25
The mean roughly increases by 2.
Consider the given table.
- The first row represents first term (first brackets):
+x+x+x-1=3x-1
- The first column represents second term (second brackets):
+x-1=x-1
- The product of (3x-1) and (x-1) is equal to the sum of all remaining terms in this table:
+x²+x²+x²-x-x-x-x+1=3x²-4x+1.
Therefore, 3x²-4x+1=(3x-1)(x-1).
Answer: correct choice is C.
Answer:
y = -x + 7
Step-by-step explanation:
The slope formula is as follows:
y = mx + b
So, in order to get x + y = 7 into slope intercept form we have to do the following things:
- Subtract x from both sides
If you do this step then your equation should look like this:
y = -x + 7
<em>Hope this helps!!</em>
<em>- Kay</em>
Answer:
the green kin quadrant IV
Step-by-step explanation:
i took the quiz and got it right